THE ROLE OF THE CIRCASSIAN PLANT IN NATURE, IN NATURE AND UNDER THE INFLUENCE OF ABIOTIC FACTORS - Kodirova Surayyo Karshiboyevna (Web of Journals Publishing, 2025)
This article discusses the medicinal plant Circassian. Information about the structure and life cycle of the Circassian plant is provided.
Keywords: Circassian, medicinal, antimicrobial, nosebleeds, inflammation, capsella bursa-pastoris.